2022
DOI: 10.1039/d2nr02093a
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective growth of two-dimensional materials: strategies and applications

Abstract: Over the years, there have been major advances in two-dimensional (2D) materials on account of their excellent and unique properties. Among the various strategies for 2D materials fabrication, chemical vapor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…Previous studies related to area-selective growth of 2D materials have reported that fabrications of 2D materials have been conducted in seeded growth and patterned growth methods, which can control nucleation sites to suppress the random distribution of initial nuclei and achieve site-selective growth [13]. There were some studies for area-selective growth of 2D materials, which synthesized homo-or bilayer structure of transition metal dichalcogenide (TMDC) using a confined-growth method through patterning of SiO 2 masks [14], or used thermally stable PtTe 2 as an epitaxial template to form a metal-semiconductor junction [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies related to area-selective growth of 2D materials have reported that fabrications of 2D materials have been conducted in seeded growth and patterned growth methods, which can control nucleation sites to suppress the random distribution of initial nuclei and achieve site-selective growth [13]. There were some studies for area-selective growth of 2D materials, which synthesized homo-or bilayer structure of transition metal dichalcogenide (TMDC) using a confined-growth method through patterning of SiO 2 masks [14], or used thermally stable PtTe 2 as an epitaxial template to form a metal-semiconductor junction [15].…”
Section: Introductionmentioning
confidence: 99%
“…For the growth of 2D materials using CVD, substrates play significant roles, including adsorbing reactants, promoting nucleation, and stimulating epitaxial growth. 25,26 In contrast to the seeded growth in which materials nucleate from predefined seeds only in the initial stages, 27,28 substrates that are atomically flat and chemically inert at the surface provide favorable growth sites for the epitaxy of 2D materials during the entire growth process. 25,29 However, on account of the unsuitability of precursors, such as the high melting point of RE oxides (>2200 °C) 30 and the high hygroscopicity of anhydrous halides, 31 only a few individual 2D REOXs are obtained by CVD, while their synthesis is still a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…To date, mechanical exfoliation and CVD are widely used to obtain high-quality 2D nanoflakes. , However, it is difficult to produce large-area 2D REOX nanoflakes by mechanical exfoliation due to their quasi-layered structure with strong interlayer interaction, ,, impeding the comprehensive investigation of their physical properties and practical applications. For the growth of 2D materials using CVD, substrates play significant roles, including adsorbing reactants, promoting nucleation, and stimulating epitaxial growth. , In contrast to the seeded growth in which materials nucleate from predefined seeds only in the initial stages, , substrates that are atomically flat and chemically inert at the surface provide favorable growth sites for the epitaxy of 2D materials during the entire growth process. , However, on account of the unsuitability of precursors, such as the high melting point of RE oxides (>2200 °C) and the high hygroscopicity of anhydrous halides, only a few individual 2D REOXs are obtained by CVD, while their synthesis is still a significant challenge. Meanwhile, 2D heterostructures and superlattices have emerged as fascinating systems for investigating their exotic structure and physics. The epitaxial growth of the lateral heterostructures (with distinct material blocks) or superlattices (with alternating blocks) requires complex and harsh synthesis processes by CVD. , Therefore, it is highly desirable to expand a strategy for 2D REOX and lateral heterostructure synthesis.…”
Section: Introductionmentioning
confidence: 99%